Determinants of nonadherence to hypertension treatment among patients in Astana city: A pilot study - Salkhayeva, Botagoz (Nazarbayev University School of Medicine, 2018)
The purpose of this study was to assess the level of nonadherence to hypertension treatment and to identify the associated factors among patients with hypertension. This was a cross-sectional study. 48 participants were recruited at the urban polyclinic #8 in Astana city for this pilot study. The study participants were patients enrolled to the therapeutics appointment with diagnosis of hypertension. Overall, 48 patients consented to participate and filled out the self-administered questionnaires. The survey consisted of five sections, including questions on socio-demographic characteristics, health lifestyles, dietary habits, antihypertensive drug adherence, and perceptions of severity and susceptibility to hypertension, perception of barriers and benefits of hypertension treatment. Descriptive, bivariate and multivariate logistic regression analyses were conducted in Stata 12.
Keywords: Astana city; hypertension treatment; Myocardial infarction